Photon catalysis of deuterium iodide photodissociation. Issue 26 (5th December 2018) - Hilsabeck, Kallie I.; Meiser, Jana L.; Sneha, Mahima; Balakrishnan, N.; Zare, Richard N.
Abstract : The photodissociation of deuterium iodide is catalyzed by the electric field supplied by nonresonant IR photons. Abstract : A catalyst enhances a reaction pathway without itself being consumed or changed. Recently, there has been growing interest in the concept of "photon catalysis" in which nonresonant photons, which are neither absorbed nor scattered, promote reactions. The driving force behind this effect is the interaction between the strong electric field associated with a pulsed, focused laser and the polarizability of the reacting system. In this study, the effect of near-infrared, nonresonant radiation on the photodissociation of deuterium iodide is demonstrated. We use nanosecond pulses rather than time-resolved spectroscopy to investigate the average effect of the electric field on the branching ratio for forming D + I( 2 P3/2 ) and D + I( 2 P1/2 ). Changes in the measured D-atom speeds between field-free and strong-field conditions confirm substantial differences in dissociation dynamics. Both the magnitude and direction of change in the branching ratios are dependent upon the photodissociation wavelength. Experiments and theoretical calculations confirm that the mechanism for photon catalysis under these conditions is dynamic Stark shifting of potential energy surfaces rather than electric-field-induced alignment of reagent molecules.